2015 IEEE International Integrated Reliability Workshop (IIRW) 2015
DOI: 10.1109/iirw.2015.7437068
|View full text |Cite
|
Sign up to set email alerts
|

Reliability aging and modeling of chip-package interaction on logic technologies featuring high-k metal gate planar and FinFET transistors

Abstract: Despite chip-package interaction (CPI) has been extensively used in nano-electronics industry, impact of CPI stress on transistor performance and reliability remains unclear. In this work, performance change of transistor featuring HK/MG planar and FinFET by 4-point bending experiments were conducted to study stress evolution. Finite-element modeling (FEM) simulation revealed that P-FinFET mobility change is less sensitive to applied stress than planar. Device reliability as BTI/HCI and ring oscillator frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…For CMOS devices, the results of stress variations across the die leads to timing variability that must be accounted for with design margins. Prior studies by Intel [8] and TSMC [9] observed qualitatively similar results in ROs fabricated in test chips that were used to investigate the effects of package overmolding on induced stress and resulting circuit timing variation.…”
Section: E Ring Oscillator Behavior After Thinning and Temperature Cyclingmentioning
confidence: 64%
“…For CMOS devices, the results of stress variations across the die leads to timing variability that must be accounted for with design margins. Prior studies by Intel [8] and TSMC [9] observed qualitatively similar results in ROs fabricated in test chips that were used to investigate the effects of package overmolding on induced stress and resulting circuit timing variation.…”
Section: E Ring Oscillator Behavior After Thinning and Temperature Cyclingmentioning
confidence: 64%